Foreign aid as prize: Incentives for a pro-poor policy - Tejashree Sayanak; Sajal Lahiri (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
We develop a theoretical model of foreign aid to analyse a method of disbursement of aid which induces the recipient government to follow a more pro-poor policy than it otherwise would do. In our two-period model, aid is given in the second period and the volume of it depends on the level of wellbeing of the target group in the first period. We find that this way of designing aid does increase the welfare of the poor. We also consider the situations where the donor and the recipient governments act simultaneously as well as sequentially, and find that by moving first in a sequential game, the donor country can, under certain conditions, increase the welfare of the poor and its own compared to the case of simultaneous moves.
Keywords: D63; F35; 330; foreign aid; fungibility; governance; welfare; prize; Entwicklungshilfe; Good Governance; Armut; Armutspolitik; Nash-Gleichgewicht; Spieltheorie; Theorie